Tinea Capitis Kerion Type: A Case Report - Dyah Ratri Anggarini; Trisniartami Setyaningrum (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2014)
Background: Tinea capitis is a superficial fungal infection. Kerion is one of its form, which is an inflammation form due to a hypersensitivity reaction to fungal infection caused by group Mycosporum and Trichophyton. Purpose: To understand the clinical manifestation, species causing agent, and management of tinea capitis.  Case management: A four-year-old boy, 17 kg, came with a mass on the head, accompanied with pain, fever, and hair loss since 1 week before hospitalization, it appeared after playing with the neighbor's pets. General examination showed enlargement of the right preauricular lymph node. Dermatological examination revealed a mass in the head 7 cm in size with pus, partially covered with crust, and there were also warm and pain on palpation. Wood lamp examination was negative, but in potassium hydroxide examination showed spores outside and inside the hair shaft. Result of fungal cultures was T. mentagrophytes. Routine blood tests obtained only leukocytosis, which was 12.390/µL. The patient was treated with griseofulvin, erythromycin, wet dressing, and ketokonazole shampoo. It was shown good results after therapy for 8 weeks. Conclusions: Tinea capitis caused by T. mentagrophytes presenting an inflammatory reaction, causing a fungal infection in the hair shaft. Auxiliary examination for the diagnosis of tinea capitis can be done in various ways, the easiest one is by potassium hydroxide 20% examination, fungal culture is then performed to determine the species causing the infection. Therapeutic use of griseofulvin is still the main choice.Key words: tinea capitis kerion type, T. mentagrophytes, griseofulvin.